Analysis of the use of discretionary rights by members of the national police under law No. 2 of 2002 and the use of discretion in error - Edi Saputra Hasibuan (Trigin Publisher, 2023)
The National Police is an institution that is the spearhead in enforcing the law and maintaining security stability in the country, against this heavy task, it is natural that every member of the police on duty has specialization in order to face and overcome existing threats, besides that as a distinguishing factor that must be inherent in every member of the National Police, there must, the existence of this right can be a way out to solve a complicated condition in the field, on the other hand, discretionary rights can also be used incorrectly because the interpretation of people can vary, this paper will see how the proper use of discretionary rights is in accordance with the legal corridor, because every member of the National Police really must be able to understand authority through their discretionary rights properly, so that there is a proper order and legal system, as a concrete example in the eyes of every community.